1997
DOI: 10.1007/s004420050338
|View full text |Cite
|
Sign up to set email alerts
|

Early survival in roe deer: causes and consequences of cohort variation in two contrasted populations

Abstract: Time- and sex-specific summer survival of roe deer fawns was estimated using capture-mark-recapture methods in two enclosed populations living in contrasting conditions. The population of Trois Fontaines (eastern France) was roughly constant in size throughout the study period, while in Chizé (western France), the population experienced frequent summer droughts and numbers decreased continuously during the study. Early survival of fawns was low and highly variable over the years at both Chizé and Trois Fontain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
248
4
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 229 publications
(271 citation statements)
references
References 71 publications
14
248
4
1
Order By: Relevance
“…In our study, on the other hand, we did not find any evidence of an effect of climatic conditions during spring (rainfall), but found that only density accounted for long-lasting cohort effects. This was positively related to early fawn survival (Gaillard et al 1997) and winter mass of fawns (Gaillard et al 1996). Thus, roe deer at Chizé that were born during years of high density not only grew more slowly than fawns born at low density (Gaillard et al 1996), but were also unable to compensate for low initial growth (this study).…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…In our study, on the other hand, we did not find any evidence of an effect of climatic conditions during spring (rainfall), but found that only density accounted for long-lasting cohort effects. This was positively related to early fawn survival (Gaillard et al 1997) and winter mass of fawns (Gaillard et al 1996). Thus, roe deer at Chizé that were born during years of high density not only grew more slowly than fawns born at low density (Gaillard et al 1996), but were also unable to compensate for low initial growth (this study).…”
Section: Discussionmentioning
confidence: 62%
“…Lond. B (2002) juvenile survival (Gaillard et al 1997) and fawn body mass (Gaillard et al 1996), between-habitat differences in density, if they occur, did not balance between-habitat differences in quality that consistently influenced mass in all sex and age classes of roe deer (Pettorelli et al 2001). Such pervasive effects of habitat quality may result from the very sedentary habits of adult roe deer at Chizé (N. Pettorelli, J.-M. Gaillard, G. Van Laere, D. Delorme, P. Duncan and D. Maillard, unpublished data), which limit exchanges between habitats.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas most studies on ungulates document a strong impact of severe winters on juvenile survival in highly seasonal environments (e.g. Loison et al 1999;Coulson et al 2001), others suggest that spring-summer may also be a critical period, in some cases being even more important than winter (Saether et al 1996;Gaillard et al 1997). We document a die-off among lambs of mouflon (Ovis gmelini musimon × Ovis sp.)…”
Section: Introductionmentioning
confidence: 58%
“…The dynamics of this population is well known (Gaillard, Delorme, Boutin et al, 1993;Gaillard, Boutin et al, 1997;Gaillard, Liberg et al, 1998): it grew from c. 200 in 1979 to a peak of 550 in 1983 and then decreased to < 200 in the mid-1990s owing to both density-dependent responses of recruitment and severe summer droughts in the late 1980s. In roe deer, births are highly synchronized and occur mostly in May (with 80% of fawns being born between 5 and 25 May, Gaillard, Delorme, Jullien et al, 1993;Linnell, Wahlström & Gaillard, 1998).…”
Section: Roe Deer Populationmentioning
confidence: 99%